Split fertilization as a strategy to reduce the amount of fertilizer applied in potato crops form Colombia. Case of study - Monsalve, Oscar Iván; Espitia, Eduardo María; Bolaños-Benavides, Martha Marina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
In potato crops in Colombia, fertilization has low efficiency in terms of absorption of nutrients by the plant due to fixing, leaching or volatilization processes. To counter this phenomenon, we evaluated the effect of the split application of fertilizers on potato plants and soil. Five treatments were evaluated: Control - fertilization used by farmers locally; As - fertilization recommended by the lab; AsSplit - monthly split of lab recommendation; AsSplit25 - monthly split of lab recommendation, reduced globally by 25%; AsSplit50 - monthly split of the lab recommendation, reduced globally by 50%. AsSplit treatment generated the highest yield (34.13 t ha-1), while treatments that reduced the amount of fertilizer by 25% and 50% obtained the lowest yield (30.94 and 29.57 t ha-1, respectively). However, they generated the lowest amount of NO3- in the leachate measurements at 30 and 90 cm deep. Our results suggest that designing the fertilization formula and applying it according to the requirements of the potato plant and soil fertility generates a positive effect on yield crop and environmental.